Ethnic Differences in Vitamin D Status: a Comparative Study among Indian and Malaysian Medical Students - Ambiger, Sudha; Kulkarni, Sushma; P. Hadimani, Chetana; Javali, Shivalingappa; M. Shindhe, Varsha; Farheen, Fatima; V Dhangi, Arun; Ahmad Zuki Bin Nik Lah, Nik (Journal of Neonatal Surgery, 2025)
Background: The prevalence of vitamin D deficiency has been increasing among healthy population. Race , ethnicity, diet, sun exposure, physical activity are known to be strong predictors of vitamin D. Few studies have investigated the vitamin D status of Malaysia and India. But there is no comparative study of Vitamin D status among medical students of Indian and Malaysian ethnicity. The present study is undertaken to assess vitamin D status among students of Indian and Malaysian ethnicity, studying in medical colleges of Belagavi, India. Objectives: Materials and method: A total of 100 apparently healthy Medical students aged between 18 and 25 years studying in medical colleges of Belagavi were included. The study participants were divided into two groups; 50 Malaysian medical students and 50 Indian medical students. Students who are taking adequate dietary intake of Vitamin D > 10 μg /d (assessed by validated food frequency questionnaire) 15 were included in the study. All participants were asked regarding physical activity( IPAQ-Short), sun exposure, (Veritable Sun Exposure= multiplying daily sun exposure in hours and BSA (%)) ,sun protection behavior(Sun protection score (Sun protection score was derived through the sum of usage of sun block lotion, veil, cap/hat, long sleeve shirt, gloves, long pants, long skirts and umbrella (max = 8, min = 0) and detailed dietary intake (by food frequency questionnaire ). Vitamin D analysis done by commercially available kit , by florescent immunoassay. Bone markers calcium, phosphorus and alkaline phosphatase estimated by commercially available kit by autoanalyser.. Results: Indian group has more vitamin D deficient students 39(78%) compared to Malaysian group 33(66%). In Malaysian group 9(18%) insufficient and 6 (12%) sufficient. In Indian group 6(12%) insufficient and 5(10%) sufficient. There is a no statistically significant difference in Vitamin D level between Malaysian group and Indian group. There was no significant difference between Malaysian group and Indian group regarding the level of vitamin D, Phosphorus and alkaline phosphatase. Calcium levels were low in both the groups, with the mean of 8.80±1.14 in Malaysian group and 8.07±1.09 in Indian group and difference between the groups was statistically significant (p<0.05). There was statistically significant (P <0.05) positive correlation between vitamin D and sun exposure in hours, milk intake, physical activity in total group, Malaysian group and Indian group. There was significant (P <0.05) negative correlation between vitamin D and sun protection score in total group, Malaysian group and Indian group. Sun exposure, sun protection score, milk intake and physical activity shows statistically significant value (p<0.05) with different vitamin D (deficiency, sufficient and insufficient) levels. Conclusion: Medical students with, lower milk intake, reduced sunlight exposure, less physical activity and frequent use of sun protection are more likely to experience vitamin D deficiency. This leads to alterations in calcium and phosphorus metabolism and elevated ALP levels, which reflect increased bone turnover. These biochemical imbalances not only affect bone health but may also impact overall well-being. The present study conducted on Indian and Malaysian medical students reinforces the importance of maintaining adequate vitamin D levels for optimal mineral metabolism and bone health. There is a need for increased awareness about the importance of adequate sun exposure, a balanced diet rich in vitamin D, and engaging in outdoor activities to optimize vitamin D levels among medical students